Attenuation of reactive gliosis does not affect infarct volume in neonatal hypoxic-ischemic brain injury in mice. - Katarina Järlestedt; Catherine I Rousset; Maryam Faiz; Ulrika Wilhelmsson; Anders Ståhlberg; Hana Sourkova; Marcela Pekna; Carina Mallard; Henrik Hagberg; Milos Pekny (PLoS ONE)
Background Astroglial cells are activated following injury and up-regulate the expression of the intermediate filament proteins glial fibrillary acidic protein (GFAP) and vimentin. Adult mice lacking the intermediate filament proteins GFAP and vimentin (GFAP(-/-)Vim(-/-)) show attenuated reactive gliosis, reduced glial scar formation and improved regeneration of neuronal synapses after neurotrauma. GFAP(-/-)Vim(-/-) mice exhibit larger brain infarcts after middle cerebral artery occlusion suggesting protective role of reactive gliosis after adult focal brain ischemia. However, the role of astrocyte activation and reactive gliosis in the injured developing brain is unknown. Methodology/principal findings We subjected GFAP(-/-)Vim(-/-) and wild-type mice to unilateral hypoxia-ischemia (HI) at postnatal day 9 (P9). Bromodeoxyuridine (BrdU; 25 mg/kg) was injected intraperitoneally twice daily from P9 to P12. On P12 and P31, the animals were perfused intracardially. Immunohistochemistry with MAP-2, BrdU, NeuN, and S100 antibodies was performed on coronal sections. We found no difference in the hemisphere or infarct volume between GFAP(-/-)Vim(-/-) and wild-type mice at P12 and P31, i.e. 3 and 22 days after HI. At P31, the number of NeuN(+) neurons in the ischemic and contralateral hemisphere was comparable between GFAP(-/-)Vim(-/-) and wild-type mice. In wild-type mice, the number of S100(+) astrocytes was lower in the ipsilateral compared to contralateral hemisphere (65.0+/-50.1 vs. 85.6+/-34.0, p<0.05). In the GFAP(-/-)Vim(-/-) mice, the number of S100(+) astrocytes did not differ between the ischemic and contralateral hemisphere at P31. At P31, GFAP(-/-)Vim(-/-) mice showed an increase in NeuN(+)BrdU(+) (surviving newly born) neurons in the ischemic cortex compared to wild-type mice (6.7+/-7.7; n = 29 versus 2.9+/-3.6; n = 28, respectively, p<0.05), but a comparable number of S100(+)BrdU(+) (surviving newly born) astrocytes. Conclusions/significance Our results suggest that attenuation of reactive gliosis in the developing brain does not affect the hemisphere or infarct volume after HI, but increases the number of surviving newborn neurons.